2018
DOI: 10.3389/fneur.2018.00319
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Mapping Correlates of Impaired Eye Movement Control in Parkinsonian Syndromes: A Systems-Based Concept

Abstract: The investigation of the human oculomotor system by eye movement recordings provides an approach to behavior and its alterations in disease. The neurodegenerative process underlying parkinsonian syndromes, including Parkinson’s disease (PD), progressive supranuclear palsy (PSP), and multisystem atrophy (MSA) changes structural and functional brain organization, and thus affects eye movement control in a characteristic manner. Video-oculography has been established as a non-invasive recording device for eye mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Our data showed that the incidence of hypometria in MSA was prominently higher than PD, and hypermetria could only occur in MSA, which is in line with the report by Gorges et al (Gorges et al., 2014 ). Hypometria in PD may be attributed to the irregular pulse in omnipause neurons of the brainstem or cortical dysfunction, whereas hypometria and hypermetria in MSA were mainly due to impairment of the cerebellum (Gorges et al., 2018 ; Gorges et al., 2013 ; R. John Leigh, 2015 ). So compared with PD, hypometria and hypermetria may be a unique ocular change in MSA.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the incidence of hypometria in MSA was prominently higher than PD, and hypermetria could only occur in MSA, which is in line with the report by Gorges et al (Gorges et al., 2014 ). Hypometria in PD may be attributed to the irregular pulse in omnipause neurons of the brainstem or cortical dysfunction, whereas hypometria and hypermetria in MSA were mainly due to impairment of the cerebellum (Gorges et al., 2018 ; Gorges et al., 2013 ; R. John Leigh, 2015 ). So compared with PD, hypometria and hypermetria may be a unique ocular change in MSA.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were recruited using the following criteria: (1) 45 to 80 years old; (2) no sign of dementia according to the Chinese version of the Mini-Mental State Examination, 30 with education-based cutoffs validated in Chinese populations 31 ; (3) no history of intracranial surgery or traumatic brain injury; (4) no psychiatric disorders; (5) no alcoholism; (6) no history of severe eye disease; (6) not taking any medication known to affect the oculomotor system; and (7) no history of other neurological disorders.…”
Section: Participantsmentioning
confidence: 99%
“…The investigation of the oculomotor system by recording eye movements provides valuable information about the localization and pathoanatomy of many neurodegenerative diseases. 7,8 A variety of eye movement abnormalities (eg, impaired saccades and smooth pursuit) are commonly observed in synucleinopathies, 9 with some abnormalities appearing in the very early stage of synucleinopathies 10,11 and deteriorating with disease progression. 12,13 Because iRBD and synucleinopathies share similar pathological changes in the central and peripheral nervous systems, 14,15 eye movement abnormalities might already be present in iRBD.…”
mentioning
confidence: 99%
“…In the absence of a relation to disease progression, the suitability as a progression marker must be considered to be limited. However, with respect to the association with pathological changes in the brain, correlations between the reduction of the maximum vertical saccade velocity and macro-and microstructural as well as functional damage to the midbrain has been shown by advanced neuroimaging approaches [15,16,30,31].…”
Section: Vog Findings In the Light Of The Oculomotor Parameters Of Thmentioning
confidence: 99%